(untitled) (Islas, 2024)
Introduction: The initial situation, or orientation, is the part of conversational narratives that establishes the topic or point of the story and identifies the time and place where the events occurred. Methods: The hermeneutic method, incorporating tools from linguistic discourse analysis, was used in the research to guide methodological choices and focus, as well as for sample interpretation. The study considers language in use, which is essential for research with a pragmatic orientation. Results: A specific analysis is presented, taking into account the specific characteristics of the analyzed text type for studying the observed linguistic phenomenon. This approach ensures the adaptation of the findings to the specific communicative situation, allowing comparisons with similar studies conducted in other geographic locations, which can enable generalizations about the described behavior. Conclusions: Spatial perception allows for the adoption of a specific referential anchorage for each conversational narrative, which is influenced by the story’s argumentative objective, the described physical environment, and the personal experiences of the narrator.